The Influence of Religious Social Interactions on the Economy of the Bengkarek Community in West Kalimantan - Sulaiman; Tiara Sari; Agustina (International Journal of Sociology of Religion, 2025)
Religious social interaction in society is one of the important aspects that can influence various dimensions of life, including the economy. This study aims to analyze the influence of religious social interaction on the local economy in Bengkarek Village, West Kalimantan. In a society with a Muslim majority, religious social interaction plays a significant role in shaping social and economic life patterns. This research uses a qualitative methodology with a religious sociology approach, with data collection conducted through direct observation, interviews, and documentation. Data analysis was performed through data condensation, data display, and drawing conclusions. The results of this study show that religious social interaction between Islam and Catholicism in Bengkarek, West Kalimantan, has formed a relationship pattern based on mutual respect, enriching the local community's life. In the context of the economy, this interfaith harmony opens opportunities for cooperation in various sectors, such as trade, education, and joint ventures. This harmony accelerates local economic development by fostering trust, supporting social solidarity, and expanding economic networks between individuals or groups. However, the influence of religion also faces challenges, such as potential minor conflicts that could disrupt stability, although positive interactions tend to dominate.